Lessons from Covid-19. Anticipatory breach as a feasible alternative to force majeure and hardship under Art. 79 CISG - Lozano Hernández, Julián (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Article 79 of the United Nations Convention on Contracts for the International Sale of Goods imposes very strict requirements for its application as a ground for exemption from liability. As an alternative to it and in line with modern relational contracts theories, this article proposes, in situations where there are circumstances that prevent a normal development of the contract, the use of the anticipatory breach mechanism contained in Articles 71 to 73 of the Convention, especially for contracts of a certain complexity and of medium and long term, such as supply contracts.